2011
DOI: 10.1101/gad.2069311
|View full text |Cite
|
Sign up to set email alerts
|

Translational repression of p53 by RNPC1, a p53 target overexpressed in lymphomas

Abstract: The p53 pathway is critical for tumor suppression, as the majority of human cancer has a faulty p53. Here, we identified RNPC1, a p53 target and a RNA-binding protein, as a critical regulator of p53 translation. We showed that ectopic expression of RNPC1 inhibited, whereas knockdown of RNPC1 increased, p53 translation under normal and stress conditions. We also showed that RNPC1 prevented cap-binding protein eIF4E from binding p53 mRNA via its C-terminal domain for physical interaction with eIF4E, and its N-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
183
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 117 publications
(206 citation statements)
references
References 59 publications
21
183
0
Order By: Relevance
“…While p73 transcription and protein stability have been extensively investigated, little is known about whether p73 is regulated by posttranscriptional mechanisms, such as mRNA stability. Previously, we showed that RNPC1 is a target of members of the p53 family, including p73 (31,44,45). In this study, we further found that ectopic expression of TAp73␣ or TAp73␤ increased the expression of RNPC1 in SW480 and p53 Ϫ/Ϫ HCT116 cells ( Fig.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…While p73 transcription and protein stability have been extensively investigated, little is known about whether p73 is regulated by posttranscriptional mechanisms, such as mRNA stability. Previously, we showed that RNPC1 is a target of members of the p53 family, including p73 (31,44,45). In this study, we further found that ectopic expression of TAp73␣ or TAp73␤ increased the expression of RNPC1 in SW480 and p53 Ϫ/Ϫ HCT116 cells ( Fig.…”
Section: Resultssupporting
confidence: 61%
“…Previously, we showed that RNPC1 is a target of the p53 family, including p73, and in turn, RNPC1 posttranscriptionally regulates the p53 family, including p53 and p63 (31,44,45). Here we further found that ectopic expression of p73 increases RNPC1 expression whereas knockdown of p73 decreases it (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The other possibility is that Ninj1-mediated signals may modulate the assembly of translation initiation complex such as eIF4F complex (4E+4G+4A), eIF4B, and poly(A)-binding protein (33). For example, RNPC1, also called Rbm38, is a p53 target, which, in turn, represses p53 mRNA translation by preventing eIF4E from binding to p53 mRNA (22).…”
Section: Lack Of Ninj1 Up-regulates P53 Expression Potentially Throughmentioning
confidence: 99%
“…Cell Line Generation-Cf2Th cells that can inducibly express HA-tagged wild-type dog p21, dog p21(S123A), and dog p21(S123D), were generated by using a Tet-on inducible system as described previously (33,34). Briefly, pcDNA4 vectors containing HA-tagged wild-type dog p21, dog p21(S123A), or dog p21(S123D) were transfected into Cf2Th cells expressing a tetracycline repressor (pcDNA6).…”
Section: Methodsmentioning
confidence: 99%